Technical Challenges Posed by ADHD in the Opening Phase of Analysis: A Candidate's Reflections. Issue 1 (1st January 2019) - Whiteside, Kristin
ABSTRACT: This paper describes the case of a man diagnosed with attention deficit hyperactivity disorder (ADHD) since childhood who struggled to engage in a transition from psychotherapy to psychoanalysis. The analyst's efforts to establish an analytic frame did not take into account the ways in which his development and adulthood were both compromised by the presence of ADHD. Despite the patient's intentions to immerse himself in analytic treatment, his actions and associations revealed a resistance to observing himself. With a retrospective lens, the author considers how she might have engaged with him in a manner that better accounted for his narcissistic vulnerability, weaknesses in affect regulation, and executive dysfunction.